Investigation of INDEL variants in apoptosis: the relevance to gastric cancer - Giovanna Chaves Cavalcante; Milene Raiol de Moraes; Cristina Maria Duarte Valente; Caio Santos Silva; Antônio André Conde Modesto; Paula Baraúna de Assumpção; Paulo Pimentel de Assumpção; Sidney Santos; Ândrea Ribeiro- (BMC, 2020)
Abstract Background Apoptosis is a type of cell death involved in different pathways inherent to the cell and the evasion from this mechanism has been related to cancer, although this process remains not very well comprehended. Gastric cancer (GC) is one of the most incident and aggressive types of cancer worldwide. In this study, we analyzed the distribution of INDEL variants in GC patients (Case) and individuals from the general population (Control) from the Amazon region, in which GC is remarkably frequent. Methods A panel of nine INDEL markers in apoptosis-related genes (BCL2 rs11269260, CASP3 rs4647655, CASP8 rs3834129 and rs59308963, CASP9 rs4645982 and rs61079693, FADD rs4197, FAS rs10562972 and TP53 rs17880560) was developed and genotyped by multiplex PCR in both groups. Results In our analyses, only marker rs4197 (FADD gene) was associated to GC development as follows: INS/DEL genotype of rs4197 increasing in about 2-fold the chances of developing this type of cancer (P = 0.046; OR = 1.940; 95%CI = 1.011-3.725). Conclusion Our results suggest that rs4197 (FADD gene) might play a role in gastric carcinogenesis in the investigated population. More studies are needed to clarify this relation. Here, we highlight the importance of investigating INDEL variants in genes involved in apoptosis.